Agricultural Modernization Communication Network in the City of Serang Banten Indonesia - Sigit Surahman (Future Science, 2022)
The population density in Serang town has a control the narrowing agricultural. This was the start the concept of slim land farming as food security. the ladies Farmers cluster (KWT) is an alternate thanks to strengthen food security, particularly throughout the Covid-19 amount that occurred in 2020. This analysis can describe the method of its formation through communication actions. 1) however did KWT Annisa amendment ancient farming designs into fashionable ones?; 2) what's role individual vocals in farmer groups?. The idea of communication is that the basis for knowing act of communication. Case studies square measure used as a technique during this analysis. Interviews, observations, and agricultural land information from the Central Statistics Banten became the sources for this analysis. The ultimate analysis shows the results of vocal opinion leaders being the middle that's ready to encourage the utilization of slim land.